Standards of pathology in the diagnosis of systemic mastocytosis: recommendations of the EU-US Cooperative Group - Sotlar, Karl; George, Tracy I.; Kluin, Philip; Reiter, Andreas; Schwaab, Juliana; Panse, Jens; Brockow, Knut; Hartmann, Karin; Sperr, Wolfgang R.; Kristensen, Thomas; Nedoszytko, Boguslaw; Carter, Melody; et al. (The journal of allergy and clinical immunology. In practice, 2022)
Pathology plays a central role in the diagnosis of systemic mastocytosis (SM), its delineation from other neoplasms and reactive conditions, and in monitoring of SM under therapy. The morphologic hallmark of SM is the accumulation of spindle-shaped, hypogranulated mast cells (MCs) in bone marrow (BM) and other extracutaneous tissues. Four of the 5 World Health Organization-defined diagnostic criteria (ie, compact MC aggregates [=major criterion]; atypical MC morphology; activating KIT point mutations; aberrant expression of CD25 and/or CD2 and/or CD30 in MCs [=minor criteria]) can be addressed by the pathologist. The final classification of SM variants as either BM mastocytosis, indolent SM, smoldering SM, aggressive SM (ASM), SM with an associated hematologic neoplasm (SM-AHN), or MC leukemia (MCL) has important prognostic significance and requires the integration of certain morphological, clinical, radiological, and biochemical data, referred to as B- and C-findings. Substantial diagnostic challenges may be posed to the pathologist and clinician especially in the so-called advanced SM variants, that is, ASM, MCL, and SM-AHN. In this article, updated recommendations of the EU-US Cooperative Group regarding standards of pathology in the diagnosis of SM, presented during the year 2020 Working Conference held in September in Vienna, are reported.